Deep Learning–Guided Prediction of Phase Separation–Driven Transcriptional Reprogramming in YAP-MAML2 Fusion Oncoproteins - Jakub C. Washington (International Journal of Clinical and Translational Medicine, 2026)
Recent advances in molecular biology have revealed that aberrant phase separation of fusion oncoproteins represents a critical mechanism driving transcriptional reprogramming in aggressive cancers. The YAP-MAML2 fusion oncoprotein, frequently identified in epidermoid and mucoepidermoid carcinomas, undergoes liquid-liquid phase separation to form dynamic condensates that selectively sequester transcriptional coactivators and remodel gene expression networks. While this phenomenon has been experimentally validated, the biophysical complexity and combinatorial diversity of phase separation events present significant challenges for systematic prediction and therapeutic targeting. This article proposes a deep learning-guided computational framework designed to predict phase separation-driven transcriptional reprogramming induced by YAP-MAML2 fusion variants. The framework integrates multimodal data sources, including structural protein features, condensate biophysical parameters, and chromatin interaction maps, to model the emergent regulatory logic of phase-separated transcriptional hubs. A systems-level perspective is adopted to examine infrastructure dependencies, data governance challenges, model robustness, and the sustainability of deploying such predictive architectures in clinical and research settings. Key architectural trade-offs between predictive accuracy, interpretability, and computational cost are analyzed through comparative case illustrations involving related intrinsically disordered proteins and fusion-driven condensates. The discussion extends to policy implications surrounding algorithmic fairness in oncoprotein modeling, reproducibility of deep learning predictions across heterogeneous biological contexts, and the ethical governance of AI-guided therapeutic discovery. By bridging deep learning engineering with phase separation biology, this work provides a foundational blueprint for scalable, predictive, and responsible deployment of computational tools in the study of fusion oncoprotein condensates.